Research Developments Analysis on Gold Nanoparticles (AuNPS) as Antimicrobial Agents through Bibliometric Computational Mapping using VOSviewer - Thyta Medina Salsabila Erlangga; Asep Bayu Dani Nandiyanto (Jurnal Kimia Fullerene, 2022)
The many uses of gold nanoparticles in the biomedical field, including as an antimicrobial agent, prompted us to analyze the development of gold nanoparticles as antimicrobial agents research through a bibliometric approach with computational mapping analysis. The publication data used are publications from the Google Scholar database using the Publish or Perish Reference Manager software. The article's title, abstract, and publication year are used as a reference in processing publication data to make it more relevant and specific to the related topic, and the data is visualized by VOSviewer software. Found 257 highly relevant publication articles on related issues indexed by Google Scholar during the last ten years (2013 to 2022). The results show that research on associated topics has developed well because the number of publications has not decreased from 2013-2021, and until August 2022, the number of publications reached an amount equivalent to the number of publications in 2015-2017. The bibliometric results show that the publication trend of gold nanoparticles as antimicrobial agents is directed at studies on antimicrobial effect, antimicrobial property, and antiviral activity. The results of this study are expected to be used as a first step for further research on related topics.